PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN DI SHOP AND DRIVE - Auladi, Syafaat Auladi; Damaiyanti, Elsa Rizki; Juniarto, Tuwandi; Damayanti, Nadia Eka (Jurnal Liga Ilmu Serantau, 2025)
This study explores the impact of Total Quality Management (TQM), a management approach focused on continuous quality improvement involving all organizational components, on employee performance at Shop and Drive, an automotive service provider. In a highly competitive business environment, enhancing human resource quality is essential to maintain excellent service delivery. The research employs multiple linear regression analysis using data collected from Shop and Drive employees. The findings reveal that while the influence of TQM on performance is not entirely statistically significant, its consistent implementation contributes positively to work efficiency, customer satisfaction, and the company’s competitiveness. These insights offer valuable input for management in formulating sustainable service quality improvement strategies.